The Impact of Resource Management on Business Performance - Slavica Singer; Ivana Šandrk Nukić (Ekonomski Vjesnik, 2013)
Human Resource Management (HRM) is part of the overall business strategy of any company. In order to control the implementation of a business strategy, it is essential to take into account the impact of HRM on business performance, i.e., company’s competitiveness. This paper sets out to answer how to measure the impact of HRM on business performance and based on that define priority HRM activities for a particular company. In view of the above, the paper reviews relevant scientific articles using primarily scientific methods such as analysis and synthesis of scientific knowledge in the field of strategic management and human resource management. In addition, the paper presents some results of the empirical research conducted in mid-sized construction companies in Croatia using a questionnaire. These results point to specific HRM activities that have a significant impact on business performance.